Sigurd Aa. Aarnes in memoriam - Bugge, K. E. (Grundtvig-Studier, 2007)
Sigurd Aa. Aarnes in memoriam By K. E. Bugge K. E. Bugge’s obituary for Sigurd Aa. Aarnes, professor of history and literary scholar, University of Bergen, lays weight upon his contributions in three areas: historiography in his doctoral thesis Grundtvig’s view of history and his view of life from 1961 with its structural analysis of the two-worlds motif, literary history with a special interest in shared Danish-Norwegian literature, and identityhistory with researches into Norwegian nation-building especially after 1814. Aarnes also collaborated in planning of the historical section of the forthcoming German translation of Grundtvig, and left among his papers a completed manuscript of a textual-critical edition of Bjørnson’s story Synnøve Solbakken.